Agile Software Development with HP Agile Manager - Tal, Liran; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2015)
Agile development practices have been widely adopted in a variety of organizations, yet only a few tools are available to help make the practical process of managing agile teams less painful and more successful. HP Agile Manager is a purpose-built SaaS-based Agile planning tool. HP Agile Manager provides a simpler, smarter way to manage collaborative development. Liran Tal provides a practical, concise approach to using Agile Manager in a variety of settings to better plan, conduct, and manage software releases within development teams. His step-by-step approach will show you how to plan your product’s features, streamline the agile sprint process, work with user stories, and track defects throughout the development process. Agile Manager can work for small startups, mid-sized teams, as well as scale up for bigger organizations as a cost-effective and flexible tool to apply agile techniques to improve your software development process.
Keywords: Computers; Information Systems and Communication Service